Noise modeling of an optically controlled mesfet (OPFET) - Chakrabarti P.; Jha V.; Kalra P.; Gupta G. (My University, 2025)
The noise performance of an optically controlled MESFET (OPFET) has been reported for the first time. An equivalent noise model of the OPFET has been developed for computation of the noise-equivalent power (NEP) and signal-to-noise ratio at the output of the OPFET. The variations of NEP and SNR with the operating frequency and optical power density have also been carried out. The IC compatibility of the device will make it especially attractive for use in MMICs and OEICs.